1997
DOI: 10.1037/0022-006x.65.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in depressive symptoms in adolescence: Comparison of national samples of clinically referred and nonreferred youths.

Abstract: Gender differences in depressed mood, a syndrome of mixed anxiety-depression, and an analogue of major depressive disorder were compared in parents' and adolescents' reports in 2 large, demographically matched national samples of clinically referred and nonreferred adolescents. Referral status accounted for the greatest share of the variance in these problems. Gender differences were moderate in size and consistent in referred youths, with referred girls scoring higher than referred boys on all measures, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
74
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 20 publications
17
74
1
3
Order By: Relevance
“…the Center for Disease Control, for the year 2005-2006, found a depression prevalence between 4% and 6.4% in adolescents aged 12 to 17, without testing for gender differences ) [42]. We also had a higher prevalence in girls than boys, as found in many epidemiological studies [43][44][45]. Therefore, the higher prevalence of depression in girls than boys may not be a consequence of differential perceptions of family relationships.…”
Section: Discussionsupporting
confidence: 52%
“…the Center for Disease Control, for the year 2005-2006, found a depression prevalence between 4% and 6.4% in adolescents aged 12 to 17, without testing for gender differences ) [42]. We also had a higher prevalence in girls than boys, as found in many epidemiological studies [43][44][45]. Therefore, the higher prevalence of depression in girls than boys may not be a consequence of differential perceptions of family relationships.…”
Section: Discussionsupporting
confidence: 52%
“…Given that most youth never experience clinically significant behavioural or emotional problems, it is likely that the results of studies that focus only on mean-level change in a sample are significantly affected by the presence of a small group of youth who show extreme symptom levels over time (Compas et al, 1997). Indeed, only a relatively small group of young adolescents can be labelled 'high risk' (Bry, 1982).…”
Section: Introductionmentioning
confidence: 98%
“…However, boys were much more prone to have school-related disabilities, whereas girls were more likely to have family-related disabilities, even when diagnostic status was controlled. Although a number of studies have suggested that gender may affect the manifestations of some disorders (Andersen & Teicher, 2000 ;Arnold, 1996 ;Compas et al, 1997 ;Gaub & Carlson, 1997 ;Lewinshon, Gotlib, Lewinshon, Seeley, & Allen, 1998 ;Schraedley, Gotlib, & Hayward, 1999 ;Stewart, Taylor, & Baker, 1997), and Riley et al (1998) reported that among young people with emotional and disruptive disorders boys had worse social functioning, we found no interactions between gender and diagnosis in relation to disability, so it appeared that each diagnosis had roughly equal implications for the presence of disability in boys and girls.…”
Section: Effects Of Demographic Characteristicsmentioning
confidence: 99%